Agricultural impacts due to Mohonpur rubber dam project in Dinajpur district of Bangladesh - Md. Faruk Hossain; Rifayat Khan Shishir2 (National Geographical Journal of India, 2024)
The present paper aims to demonstrate the agricultural impacts due to Mohonpur rubber dam project in Dinajpur district of Bangladesh. This dam provides irrigation coverage for 1000 hectares of Boro rice cultivation. The study employs a mixed-method approach, combining quantitative and qualitative data. It includes 135 household surveys, four key informant interviews, and three focus group discussions. The study findings revealed that agriculture experienced a favorable impact, with a 31 percent rise in yield production contributing to the enhanced agricultural production. The findings indicate positive agricultural impacts, with a notable 31 percent increase in yield production, contributing to enhanced agricultural productivity. A significant observation was that 33 percent of respondents noted changes in irrigation sources, with 88 percent utilizing dam reservoirs, thereby reducing dependence on groundwater sources. Additionally, 27 percent reported an expansion in crop land, while 78% reported increased crop production. Availability of fish population had also experienced a significant augmentation. Over the past decade, the rubber dam has significantly facilitated many farmers in producing more agricultural products while lowering their irrigation costs. The abundant flow of water has also benefited the fishermen of the area. The study identifies various agricultural impacts and highlights performance constraints. It concludes with recommendations.